One Size Does Not Fit All—Addressing the Complexity of Food System Sustainability - Ng'endo, Mary; Connor, Melanie (Frontiers in Sustainable Food Systems, 2022)
Food system sustainability has been highlighted as one of the major strategies to ensure healthy diets. A plethora of approaches to stabilize food systems have been suggested, including agroecology, climate-smart agriculture, and other forms of sustainable agriculture. However, a disconnect between sustainable production and consumption exists, which may hinder further progress towards achieving Sustainable Development Goal 2. This discourse was needed to connect these intersectional perspectives. To meet this need, we bring together the disconnected socio-environmental pillars and show how together they contribute to the food system sustainability agenda. We discuss the complexity of food system sustainability to cater to different geographies, building on evidence from development projects worldwide. We account for factors such as the need to incorporate intersectionality factors, food-system-related policy issues, food waste, food injustice, and undernutrition. While these intersectional inequalities can be solved through various human interventions, policy implementation, and dietary choices, we found that connecting the different policymakers remains a significant challenge for a sustainable food system. We propose implementing specific food system sustainability strategies that will be useful for policymakers and other stakeholders to enable the inclusion of a socio-environmental perspective for food systems that connect agricultural production with consumption.